Exploring the potential of halotolerant bacteria from coastal regions to mitigate salinity stress in wheat: physiological, molecular, and biochemical insights - Aizaz, Muhammad; Lubna,; Ahmad, Waqar; Khan, Ibrahim; Asaf, Sajjad; Bilal, Saqib; Jan, Rahmatullah; Asif, Saleem; Waqas, Muhammad; Khan, Abdul Latif; Kim, Kyung-Min; AL-Harrasi, Ahmed (Frontiers in Plant Science, 2023)
Salinity stress, a significant global abiotic stress, is caused by various factors such as irrigation with saline water, fertilizer overuse, and drought conditions, resulting in reduced agricultural production and sustainability. In this study, we investigated the use of halotolerant bacteria from coastal regions characterized by high salinity as a solution to address the major environmental challenge of salinity stress. To identify effective microbial strains, we isolated and characterized 81 halophilic bacteria from various sources, such as plants, rhizosphere, algae, lichen, sea sediments, and sea water. We screened these bacterial strains for their plant growth-promoting activities, such as indole acetic acid (IAA), phosphate solubilization, and siderophore production.Similarly, the evaluation of bacterial isolates through bioassay revealed that approximately 22% of the endophytic isolates and 14% of rhizospheric isolates exhibited a favorable influence on seed germination and seedling growth. Among the tested isolates, GREB3, GRRB3, and SPSB2 displayed a significant improvement in all growth parameters compared to the control. As a result, these three isolates were utilized to evaluate their efficacy in alleviating the negative impacts of salt stress (150 mM, 300 mM, and seawater (SW)) on the growth of wheat plants. The result showed that shoot length significantly increased in plants inoculated with bacterial isolates up to 15% (GREB3), 16% (GRRB3), and 24% (SPSB2), respectively, compared to the control. The SPSB2 strain was particularly effective in promoting plant growth and alleviating salt stress. All the isolates exhibited a more promotory effect on root length than shoot length. Under salt stress conditions, the GRRB3 strain significantly impacted root length, leading to a boost of up to 6%, 5%, and 3.8% at 150 mM, 300 mM, and seawater stress levels, respectively. The bacterial isolates also positively impacted the plant's secondary metabolites and antioxidant enzymes. The study also identified the WDREB2 gene as highly upregulated under salt stress, whereas DREB6 was downregulated. These findings demonstrate the potential of beneficial microbes as a sustainable approach to mitigate salinity stress in agriculture.